Foucault’s Concept of Subjectivity and the Process of Subjectification - อุปัชฌาย์, เบญจวรรณ (CRMA Journal of Humanities and Social Sciences, 2018)
Michel Foucault’s studies on the concepts of subjectification are an attempt to overcome the limitations placing by human sciences throughout the history. These limitations are formed under the epistemological framework that based on the studies on empirical and hermeneutic concepts, which emphasize on rational and structural ideas. As a result, human is scattered across various fields, making it is difficult to understand. Due to this issue, Foucault introduced a new concept to study the human sciences, which he termed “archaeology” or the study of discursive and non - discursive formation; their links to particular knowledge and the historical process of discourse from the past to the present. Then, Foucault provided another concept calling “genealogy” to connect his study of knowledge with the mechanisms of power. According to these two concepts, Foucault recognized that human are no longer the author of their own stories. Contradicting with the main belief at that time, he believed that human’s subjectivity is not fixed however, it is fluid and changeable depending on the social conditions and self - consciousness. For him, human’s subjectivity from the field of power and relies on the relation of power within the society whereas, individuals have the ability to shape up their own self, using the arts of existence and ethic that each person possesses. He referred to this process of subjectification as the technologies of the self, which individuals can use to overcome the subjugation and become the master of their subjectivity.